AKAD TRANSAKSI UMRAH: KAJIAN KOMPARATIF ANTARA BAY DAN IJARAH - Widodo, Sugeng; Salihah Khairawati (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2023)
The growth of the number of Umrah organizing bureaus in Indonesia has increased in recent years, this is a response to the high interest of the Muslim community to perform the Umrah in the Holy Land. The problem that often arises from bureaus and Umrah service providers is a mistake in using a transaction agreement (contract). The purpose of this study was to examine the right service contract for the Umrah travel agency in accordance with the conditions and cornerstones of muamalah. This research is a descriptive qualitative study, a literature study is used to analyze the object of study, the analysis is done by comparing one contract with another contract, and conclusions drawn the most appropriate contract for Umrah service transactions. The results of the analysis concluded that the ijarah contract is the most appropriate contract for the Umrah service contract, this is in accordance with the condiiton and cornerstone of muamalah in Islam